(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
Public lighting is a service connected to the electrical distribution system of the electric energy concessionaires, which are active members of the electrical power system. The worker who performs the service and exposes himself to risk is the electrician. Some companies that provide public lighting services do not pay the danger because they are unaware of the legitimacy of the case or to avoid burdening the payroll. The objective of the present work is to evaluate if these activities are in fact dangerous, through a descriptive methodology with theoretical and legal basis, involving laws, jurisprudence and doctrines on the right to the additional dangerousness for work in the maintenance of the public lighting system. It is concluded that due to the exposure of the worker to the risks inherent to electricity, they live up to the perception of dangerousness.